Recuperación histórica del patrimonio cultural de salud en la región sur del Ecuador: estado de arte del patrimonio cultural en alimentación nutricional, Región Sur del Ecuador. Zamora Chinchipe. Zamora y el Norte del Perú Cajamarca II fase - Alba Sarango, Lupe Gabriela (2014)
The presented/displayed investigation next, is based on the macro denominated project “Historical Recovery of the cultural Patrimony of health in the South Region of Ecuador, and the North of Peru, II Phase: Zamora- Cajamarca”, that develops the Area of Human Health, has as main base to include/understand her culture, history, rural anthology and traditions that have come developing the towns from the Province of Zamora Chinchipe from remote times to the present time; for which one resorted to the support of a specific bibliography, material that has facilitated the obtaining of information about knowledge and feeding practices/nutrition of this population. It is a Descriptive study on the basis of consultations, from sources published on feeding/nutrition, in the periods native (500ac-1532), colonial (1532-1820) and republican (1820-2011); Interpretative, because the data collected in the documentary revision, were interpreted according to every investigated historical period, fulfilling specific the objectives proposed. In the Native period, the Shuar was great hunters, their nutritional base was constituted by wild vegetables of the zone; and it is so the foods cultivated in his ajashuar and those of origin animal, contributed to energy and necessary nutrients for their development. Whereas, in the colony and republic, great cultural changes arose partner, the ancestral development of science and practical technology were eliminating his knowledge and, which affected of significant form the maintenance of the health.